A sociological study of the speech representation of the volunteer movement on the materials of the social network «VKontakte» - Maltseva, Anna V.; Shilkina, Natalia E.; Pokhomova, Alesya A. (Journal of the Belarusian State University. Sociology, 2024)
The article presents a case of using the methodology of topic modelling of texts to research the out-of-text meanings of forum messages of the Russian volunteer community in the social network «VKontakte». The epistemological value and practical significance of topic modelling in the study of social phenomena and processes are demonstrated. The validity of the proposed methodology is substantiated. The features of the speech representation of the Russian volunteer movement are outlined on the example of text messages from forums of volunteer groups in the social network «VKontakte». The prospects of applying the results of the study are considered.